Predictive Effect of Positive Youth Development Attributes on Delinquency Among Adolescents in Mainland China - Zhu, Xiaoqin; Shek, Daniel T. L. (Frontiers in Psychology, 2020)
The general proposition of the positive youth development (PYD) approach is that developmental assets such as psychosocial competence can promote healthy adolescent development and reduce problem behavior. Despite that many Western studies have shown that PYD attributes are negatively related to adolescent delinquency, not all empirical findings support the negative associations. Although different dimensions of PYD attributes may bear differential relationships with delinquency, this possibility has not been properly examined so far. In addition, related studies in mainland China do not exist. Finally, the possible mediating role of life satisfaction in linking PYD attributes to delinquency has rarely been studied. To address the research gaps and understand how PYD attributes are associated with adolescent delinquency and the underlying mediating effect of life satisfaction, matched longitudinal data were collected from 2,648 mainland Chinese secondary school students (1,109 girls, Mean age = 13.12 ± 0.81 years at Wave 1) at two waves which were separated by one year. On each occasion, participants completed a questionnaire containing validated measures of PYD attributes, life satisfaction, and delinquency. Congruent with the general theoretical prediction of the PYD approach, different PYD attributes were inversely related to concurrent and future adolescent delinquency in separate regression analyses. In addition, the negative predictions were mediated by life satisfaction. When all PYD attributes were included in a single path analysis model, three findings were observed. First, two PYD dimensions, including self-identity and general PYD attributes, showed robust negative predictions on delinquency via life satisfaction. Second, prosocial attributes displayed a weak and unstable negative predictive effect. Third, cognitive-behavioral competence showed an unexpected positive predictive effect on delinquency directly or via its negative effects on life satisfaction. The present findings add value to the existing literature by revealing the predictive role of PYD attributes on life satisfaction and delinquency among mainland Chinese adolescents. The findings also reinforce the importance of investigating individual dimensions of PYD attributes simultaneously in the research field. The present study suggests that it is promising to cultivate PYD attributes as a strategy to reduce delinquency among adolescents in mainland China.